(untitled) (Stavební obzor - Civil Engineering Journal, 2018)
In this paper, the author used mine 3D software to establish the 3D geological model of Sujishan Graphite deposit, and applied geostatistics to estimate the resource, offered references for next exploration and mining. Surpac was used to set up geological database of Sujishan Graphite deposit, topographical DTM, ore body model and grade model, 3D of drilling database, also analysis the spatial grade distribution in reality. Based on geostatistics, drilling samples are composited and statistically analysed and eliminate the impact of outliers. Experimental variograms were constructed for the striking, dipping and vertical directions. Grade and resource are estimated by ordinary kriging. Comparing to the traditional estimation methods, this 3D software gives reliable estimation, which provides references for dynamic management of mine’s resource.